A + AVD for Treatment of Hodgkin Lymphoma Variant of Richter’s Transformation - Benjamin Heyman; Michael Choi; Thomas J. Kipps (Case Reports in Hematology)
Hodgkin lymphoma variant of Richter’s transformation (HvRT) is a rare complication for patients with chronic lymphocytic leukemia (CLL), with an overall poor prognosis. We present the first known case series of patients with HvRT treated with the combination of brentuximab vedotin, doxorubicin, vinblastine, and dacarbazine (A + AVD). In our series of 4 patients, two patients treated with A + AVD for HvRT had durable remissions of 40 and 42 months, while two patients had disease progression and ultimately died. Continued investigation into the optimal management for patients with HvRT is still needed.